2004
DOI: 10.1038/sj.npp.1300495
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synaptic Plasticity of Glutamatergic Synapses on Dopamine Neurons in the Ventral Tegmental Area in Response to Acute Amphetamine Injection

Abstract: Drugs of abuse activate the reward circuitry of the mesocorticolimbic system, and it has been hypothesized that drug exposure triggers synaptic plasticity of glutamatergic synapses onto dopamine (DA) neurons of the ventral tegmental area. Here, we show that just a 2 h in vivo exposure to amphetamine is sufficient to potentiate these synapses, measured as an increase in the synaptic AMPAR/NMDAR ratio. We tested the prediction that an increase in GluR1-containing AMPA receptors would result in an increase in Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 54 publications
4
57
1
1
Order By: Relevance
“…Electrophysiological studies also support a role for GluR2-lacking receptors in VTA plasticity. Bellone and Luscher (2005) detected a substantial complement of GluR2-lacking receptors in VTA DA neurons of naive rats (P15-P21), which internalized during LTD. Faleiro et al (2004) did not detect GluR2-lacking receptors in VTA DA cells of naive P15-P18 rats. GluR2-lacking receptors were not detected in VTA DA cells of naive mice (Thomas et al, 2000;Bellone and Luscher, 2006) but were added to synapses after cocaine injection (Bellone and Luscher, 2006).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Electrophysiological studies also support a role for GluR2-lacking receptors in VTA plasticity. Bellone and Luscher (2005) detected a substantial complement of GluR2-lacking receptors in VTA DA neurons of naive rats (P15-P21), which internalized during LTD. Faleiro et al (2004) did not detect GluR2-lacking receptors in VTA DA cells of naive P15-P18 rats. GluR2-lacking receptors were not detected in VTA DA cells of naive mice (Thomas et al, 2000;Bellone and Luscher, 2006) but were added to synapses after cocaine injection (Bellone and Luscher, 2006).…”
Section: Discussionmentioning
confidence: 54%
“…Our studies do not address the mechanism by which D 1 receptor stimulation activates glutamate transmission onto VTA DA neurons, but in vivo and brain slice studies support the hypothesis that D 1 receptors act directly on PFC neurons to increase their excitability and increase glutamate levels in their target regions (Park et al, 2002;Dong and White, 2003). Interestingly, bath application of amphetamine to VTA slices failed to increase the AMPA/NMDA ratio, which could indicate a locus of action outside the VTA (perhaps PFC) but might also indicate a requirement for normal excitatory synaptic transmission, which is absent in the slice preparation (Faleiro et al, 2004). Alternatively, D 1 receptors on glutamate terminals in the VTA may facilitate glutamate release, increasing AMPAR surface and synaptic expression by activity-dependent mechanisms related to those operative in LTP.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…in vivo for 6 d, and their nucleus accumbens slices were prepared 8-10 d after the last injection. Additionally, a higher AMPAreceptor/ NMDA-receptor ratio at the glutamatergic synapses in the ventral tegmental area (VTA) was associated with higher behavioral sensitization to a single dose of amphetamine in young rats (Faleiro et al 2004). These results indicate that LTP occurred rapidly in the VTA, and with a single amphetamine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that stimulant drugs enhance the ratio of AMPA/NMDA receptor-mediated glutamate neurotransmission in the VTA (Borgland et al, 2004;Boudreau and Wolf, 2005;Faleiro et al, 2004;Saal et al, 2003;Sarti et al, 2007;Ungless et al, 2001), an effect that depends on NMDA receptor neurotransmission at the time of drug treatment (Ungless et al, 2001 …”
Section: Cihr Author Manuscriptmentioning
confidence: 99%